Today’s young people and the demand for education and training - Bruni, Elsa M. (Education Sciences & Society - Open Access, 2019)
This paper develops the theme of youth education and training by following at least three fields of analysis, which are mutually interrelated. The training process, the role of educational agencies, and pedagogy will be investigated in light of a new interpretation of the image of young people and of the one of youth that is free from rhetoric and clichés. A close look will be taken to the characteristics of current anthropology trends, focusing on the impact that such categories as “fear” and “risk” exert on training processes. The ultimate aim of this investigation will be to outline the main traits of youth crisis from a pedagogical perspective in terms of a crisis of personal development and human fulfilment, which is even more important than professional fulfilment, and of the transformations affecting rational and non-rational dimensions of the person. By referring to the social condition and to the range of interpretive paradigms inherent in current epistemologies, the paper is aimedto findthe source of the demand that young people directly and indirectly express today also through non-verbal languages, alternative “signs” and “images” that do not fall within the traditional pedagogical canon. The function of pedagogy will therefore be redefined both in theory and in practice on the basis of the need to understand the real human reality, thus interpreting its needs. At the same time, the educational operariwill be re-thought, so as to ensure that in today’s reflective democracies the purpose regarded by Raffaele Laporta as the “educational absolute” is achieved. This coincides with authentic freedom, with the most accomplished form of humanization and with the highest level of personal existence, identified as essential conditions for the freedom of learning that corresponds to the freedom of life.